ABNORMAL RETURNS ON INDONESIA STOCK EXCHANGE DURING COVID-19 PANDEMIC - Sri Hermuningsih; Pristin Prima Sari; Anissa Dewi Rahmawati (UNIVERSITAS INDRAPRASTA PGRI, 2021)
COVID-19 Pandemic In Indonesia is Corona Virus Disease 2019 (COVID-19) in the World which is caused acute respiration Corona Virus2 (SARS-COV-2). It had been separating in Indonesia since 2nd March 2020. COVID-19 influence abnormal stock return in Indonesia Stock Exchange (IDX). The study aims to calculate abnormal stock return in IDX before and after COVID-19 pandemic. We use sample 31 firms listed in IDX with random sampling method in February-May 2020. The study uses compare test to analysis data with Abnormal return method from Fama (1979). We Found that market adjusted model can influence abnormal stock return before and after COVID-19 and Social distancing policy in April-May 2020. The benefit of this study is to make investment policy in stock market when event study of COVID-19 and to calculate investor behavior in stock market so that can control stock market when event study of diseases pandemic.Keywords: Abnormal Return, Efficient Market Hypothesis, COVID-19